Driving Forces on Household Solid Waste Management Behaviors: A Research for the City of Izmir, Türkiye - Guven, Elif Duyusen; Akinci, Gorkem; Temel, Dilara (Tecno Scientifica Publishing, 2023)
The proper solid waste recycling process starts at the houses with the attendance of the individuals. The presented study includes comprehensive research on the individuals’ shopping and waste generation behaviors, awareness of waste management issues, readiness and willingness for source separation, and their self-evaluation and self-annoyance about waste generation. The current study was conducted by administering a detailed questionnaire to 300 people in Zmir, Türkiye's third largest city. The relationships between the answers given and the main factors affecting waste production were determined statistically. Principal component analysis (PCA) identified the key drivers of public behavior associated with waste generation and separation at the source. Through environmental sensitivity, including proper waste management behaviors, age is discovered to be a significant factor. Family phenomena, including stable life and family budgets (32.58%), awareness of people about their inappropriate and disproportionate behaviors towards consumption and waste generation (21.28%), and the impositions of urban life (9.37%) were found to be the major factors influencing waste management habits.